The Use and Impact of Job Search Procedures by Migrant Workers in China - Tony Fang; Morley Gunderson; Carl Lin (Institute for the Study of Labor (IZA), 2015)
Job search procedures are a form of human capital investment in that they involve current investments to enhance future returns, analogous to human capital investments in areas such as education, training and mobility that yield future returns. While the theoretical and empirical literature on job search is extensive, most of it involves developed countries. There is less on developing countries and very little on China involving migrant workers in spite of their growing practical and policy importance and the fact that they are constantly engaging in job search. This paper examines the use and impact of job search procedures used by migrant workers in China by taking advantage of a rich data set on migrant workers that has information on their job search procedure as well as a wide array of other personal and human capital characteristics. Our OLS estimates indicate that there is no effect on earnings of using informal versus formal job search procedures for migrant workers in China. However, our IV results suggest that the OLS estimates are subject to severe selection bias from the fact that the choice of job search procedure is endogenous, associated with unobservable factors that affect the choice of informal versus formal procedures and that affect the earnings outcome. Our three different IV estimates designed to deal with this bias indicate that informal procedures (various aspects of family and friends) are associated with earnings that are 33 to 43 percent below the uses of more formal procedures. The decomposition results indicate that the most important variable contributing to pay advantage of those who use formal as opposed to informal procedures is education. In sum, our results suggest that policies to encourage or facilitate migrant workers using more formal job search procedures and reducing barriers that compel them to rely on informal procedures can yield better job matches with higher earnings.
Keywords: J31; J61; J64; 330; China; migrant workers; job search methods; labour market outcomes